Aptamer loaded MoS2 nanoplates as nanoprobes for detection of intracellular ATP and controllable photodynamic therapy. Issue 38 (14th September 2015) - Jia, Li; Ding, Lin; Tian, Jiangwei; Bao, Lei; Hu, Yaoping; Ju, Huangxian; Yu, Jun-Sheng
Abstract : A smart MoS2 nanoplate-based and ATP-activatable nanoprobe was designed for fluorescence imaging of intracellular ATP and controllable photodynamic therapy. Abstract : In this work we designed a MoS2 nanoplate-based nanoprobe for fluorescence imaging of intracellular ATP and photodynamic therapy (PDT) via ATP-mediated controllable release of 1 O2 . The nanoprobe was prepared by simply assembling a chlorine e6 (Ce6) labelled ATP aptamer on MoS2 nanoplates, which have favorable biocompatibility, unusual surface-area-to-mass ratio, strong affinity to single-stranded DNA, and can quench the fluorescence of Ce6. After the nanoprobe was internalized into the cells and entered ATP-abundant lysosomes, its recognition to ATP led to the release of the single-stranded aptamer from MoS2 nanoplates and thus recovered the fluorescence of Ce6 at an excitation wavelength of 633 nm, which produced a highly sensitive and selective method for imaging of intracellular ATP. Meanwhile, the ATP-mediated release led to the generation of 1 O2 under 660 nm laser irradiation, which could induce tumor cell death with a lysosomal pathway. The controllable PDT provided a model approach for design of multifunctional theranostic nanoprobes. These results also promoted the development and application of MoS2 nanoplate-based platforms in biomedicine.